2007
DOI: 10.1007/s11547-007-0139-3
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular abdominal aortic aneurysm repair and renal complications: a comparison between suprarenal and infrarenal fixation of stent grafts

Abstract: Purpose. This study was performed to compare the rate of morphological (renal infarction and/or ischaemic lesions) and functional renal complications after the suprarenal and infrarenal fixation of aortic stent-grafts for endovascular abdominal aortic aneurysm repair (EVAR). Materials and methods. We retrospectively reviewed all followup computed tomography (CT) angiograms (obtained at 1, 6 and 12 months and yearly thereafter) and laboratory data pertaining to 102 patients who underwent suprarenal (60 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
(37 reference statements)
0
6
1
Order By: Relevance
“…The findings of the present study contrast with results of several authors who have published retrospective series indicating that suprarenal endograft fixation does not have a significant effect on short (Ͻ12 months) and midterm (up to 24 months) renal function, [13][14][15][16][17][18] using serum creatinine concentration or creatinine clearance (Cockroft-Gault formula) as primary end points. Two previous studies that directly compared postoperative renal function after infrarenal and suprarenal endograft fixation, based on prospectively collected data, were published by Davey et al 15 and Forbes et al 31 in 2006. Davey et al 15 published a series of 92 patients undergoing EVAR with a suprarenal device compared with 87 patients undergoing EVAR with an infrarenal device.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of the present study contrast with results of several authors who have published retrospective series indicating that suprarenal endograft fixation does not have a significant effect on short (Ͻ12 months) and midterm (up to 24 months) renal function, [13][14][15][16][17][18] using serum creatinine concentration or creatinine clearance (Cockroft-Gault formula) as primary end points. Two previous studies that directly compared postoperative renal function after infrarenal and suprarenal endograft fixation, based on prospectively collected data, were published by Davey et al 15 and Forbes et al 31 in 2006. Davey et al 15 published a series of 92 patients undergoing EVAR with a suprarenal device compared with 87 patients undergoing EVAR with an infrarenal device.…”
Section: Discussioncontrasting
confidence: 99%
“…[9][10][11][12] Various studies in recent years have examined the effects of suprarenal vs infrarenal stent grant fixation during elective EVAR on renal function, largely suggesting no differences between the two practices, at least in the shortterm. Most of these were retrospective cohort studies, [13][14][15][16][17] some were retrospective analyses based on prospectively collected data, 9,18 and fewer followed a prospective cohort design. 19,20 Most of these series had a follow-up of up to 1 year.…”
mentioning
confidence: 99%
“…243 Other smaller studies comparing renal function after EVAR or open repair have also shown a deterioration in renal function, with one study demonstrating similar decline between types of repair 244 and two others showing greater deterioration after EVAR. 245,246 Several studies have compared suprarenal versus infrarenal fixation during EVAR, and these support a deterioration in renal function after EVAR [247][248][249][250][251][252][253] but demonstrate little difference between suprarenal or infrarenal fixation. A meta-analysis of these studies provided conflicting results according to the analytical method used and concluded that the data were insufficient to draw any strong conclusions on the impact of suprarenal fixation.…”
Section: Renal Functionmentioning
confidence: 99%
“…A relative safe effect on renal function of a suprarenal endovascular device was confirmed. Similarly, Cotroneo et al 20 studied 60 patients with an SR stent graft and 42 patients with IR fixation and concluded that the use of endografts with suprarenal fixation did not lead to any significant increase in morphological and/or functional renal complications compared with those with infrarenal fixation. Lalka et al, 2 in a prospective analysis of data from 104 patients, found that the suprarenal fixation does not cause RA stenosis, occlusion, or infarction; nor does it preclude post-EVAR renal artery intervention.…”
Section: Discussionmentioning
confidence: 99%